Anteseden Kepuasan Pasien pada Pelayanaan Klinik di Jakarta Menggunakan Kuisioner KKP 2017 dan Dampaknya terhadap Loyalitas Pasien - Joshua Borneoputra Widjaja; Albert Surya Wanasida (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2026)
Health services in a competitive era demand high service quality to meet public expectations and build patient loyalty. This study aims to examine the influence of five dimensions of service quality - namely interpersonal behavior, professionalism behavior, convenience, financial aspects, and physical environment - on patient satisfaction, and measure the impact of patient satisfaction on patient loyalty in clinic services in Jakarta. The method used was descriptive quantitative research with a Structural Equation Modeling (SEM) approach using SmartPLS version 4.1.0.9. Primary data were obtained through the KKP-2017 questionnaire filled out by 142 patients who received outpatient services at the XYZ Clinic in April 2025, using purposive sampling technique. As a result, 85.0% of the patient satisfaction variable can be influenced by interpersonal behavior, professionalism behavior, comfort, financial aspects and the physical environment, while 15.0% is influenced by other variables outside the study. And 82.6% of the patient loyalty variable can be influenced by patient satisfaction, but the other 17.4% is influenced by other variables outside the study. The findings encourage clinic management to prioritize the development of medical professionalism, transparency in financial aspects, and improving the quality of the physical environment to build patient loyalty.